2009
DOI: 10.1016/j.jcrs.2009.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes after bilateral implantation of apodized diffractive aspheric acrylic intraocular lenses with a +3.0 or +4.0 diopter addition power

Abstract: Intermediate vision at a mean reading distance of approximately 40 cm was better with the aspheric IOL with a +3.0 D add than with the aspheric IOL with a +4.0 D add, as shown by the near peak in the mean binocular defocus curve; near and distance acuity were similar between the 2 IOLs. Patients reported excellent overall quality of vision, spectacle independence, and satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 28 publications
11
58
1
1
Order By: Relevance
“…2(b), (c) really mean the multifocal function of ReSTOR or not. They are quite different from defocus curves in ReSTOR implantation patients [13][14][15]. We expected the second peak of pseudo-accommodation curvesat +2.5Dbecause the SND1 model has the addition of+3 D (+2.5D at the spectacle plane).…”
Section: Discussionmentioning
confidence: 76%
“…2(b), (c) really mean the multifocal function of ReSTOR or not. They are quite different from defocus curves in ReSTOR implantation patients [13][14][15]. We expected the second peak of pseudo-accommodation curvesat +2.5Dbecause the SND1 model has the addition of+3 D (+2.5D at the spectacle plane).…”
Section: Discussionmentioning
confidence: 76%
“…All studies 20 30,36,38,40 show that the new AcrySof ReSTOR aspheric IOL with a +3.00 D addition provides better intermediate visual performance than AcrySof ReSTOR aspheric IOL with +4.00 D addition, with no decrease for either distance or near visual acuities. It seems that the lower addition of the IOL plays an important role in the improvement of visual acuity for intermediate distances.…”
Section: Hybrid Multifocal Iols Madrid-costa Cerviño Ferrer-blascomentioning
confidence: 98%
“…Many studies 20,24,26,27,29,30,32,[35][36][37][38]40,[42][43][44][45][46][47][48][49][50] have measured the CSF after hybrid multifocal IOL implantation. It has been suggested that CSF under photopic and mesopic conditions, after multifocal IOL implantation, must be lower than that obtained after monofocal IOL implantation, but still within the normal range.…”
Section: Contrast Sensitivitymentioning
confidence: 99%
“…Estudo comparativo de desempenho óptico e resultado visual entre duas lentes multifocais difrativas: Tecnis ZMB00 e AcrySof SN6AD1 remain challenging, requiring careful patient selection since some patients could experience less clarity, decrease in contrast, and photopic phenomena when two images are overlapped (1,(5)(6)(7) . Moreover, the same optical quality cannot be expected as with a monofocal lens (3,6) .…”
Section: Multifocal Iol Sn6ad1mentioning
confidence: 99%
“…Only in the United States, two million procedures are annually performed due to an increase in early diagnoses and demands of patients who wish to maintain productivity and daily activities (1) . Multifocal intraocular lenses (IOLs) were introduced in the early 1980s and offer the benefit of promoting both near and distance vision simultaneously (2,4) .…”
Section: Introductionmentioning
confidence: 99%